Enhancing medical students` confidence and performance in integrated structured clinical examinations (ISCE) through a novel near-peer, mixed model approach during the COVID-19 pandemic - Ravanth Baskaran; Srinjay Mukhopadhyay; Sashiananthan Ganesananthan; Movin Peramuna Gamage; Nishaanth Dalavaye; Vincent Ng; Richard Bennett; Sripradha Srinivasan; Parvathy Sureshkumarnair; Robert Spencer; Harsh Bhatt; Susruta Manivannan; et al. (BMC Medical Education, 2023)
Abstract Background Near-peer medical education serves as an important method of delivering education to junior students by senior students. Due to the reduced clinical exposure because of the COVID-19 pandemic, we developed a mentorship scheme to help medical students with their Integrated Structured Clinical Examinations (ISCEs) by providing a combination of near-peer mentorship together with lecture-based teaching on a weekly basis for a 12-week period. Students attended a specialty-focused lecture every Tuesday followed by a small group teaching session organised by their tutor. Methods A longitudinal evaluative interventional study was undertaken by the international student led medical education organisation, OSCEazy. The teaching programme was organised and conducted by third year medical students to a recruited cohort of second year medical students. Students’ perceptions of ISCEs (confidence, anxiety, and overall performance) were evaluated using 5-point Likert scales while their knowledge of the specialty was assessed using 10 single best answer questions which were distributed via Google® forms at the start and end of each week. In addition, we assessed tutor perceptions of their teaching and learning experience. Results Seventy-two tutees were enrolled in the programme (mean age: 24.4, female: 77.8%). 88.9% of the participants had not attended any online ISCE teaching prior to this. They preferred in-person ISCE teaching as compared to virtual sessions [median 4.5 (IQR 4–5) vs 3 (IQR 3–4), p <  0.0001), respectively]. There was a significant overall increase in knowledge when comparing pre-session and post-session performance [mean 53.7% vs 70.7%, p <  0.0001)]. There was a significant increase in student confidence [Confidence: median 3 (IQR:3–4) vs 4 (IQR 3–4), p <  0.0001] while no change was seen in the anxiety and perception of their overall performance in an ISCE. [Anxiety: median 3 (IQR 2–4) vs 3 (IQR 3–4), p = 0.37, Performance: median 3 (IQR 3–4) vs median 3 (IQR 3–4), p <  0.0001]. The tutors reported an increase in their confidence in teaching ISCEs online [median 3 (IQR 2–3.25) vs median 4 (IQR 4–5), p <  0.0001)]. Conclusion Online near-peer teaching increases the confidence of both tutees and tutors involved while enhancing the tutees’ knowledge of the specialty. Thus, medical schools should incorporate near-peer teaching in their curriculum to enhance the student learning experience.